Consumer Behaviour Towards Retail Industry In India: Understanding the Dynamics of Consumer Behaviour in the Indian Retail Industry (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Consumer behaviouris the study of when, why, how, and where people do or do not buy a products/services. It blends elements from psychology,sociology,social anthropologyand economics.The Indian retail sector is highly fragmented with 92 per cent of its businessbeing carried out by unorganized retailers like traditional family run smallstores and corner stores (*Source: India Brand Equity Foundation). Theorganized retail however is at a very nascent stage, though attempts are madeto increase its proportion to 9-10 percent. Retail sector is the largest sourceof employment after agriculture and has deep penetration in to the rural India.Retail is India’s largest industry, accounting for appox. 14.2 per cent of thecountry’s GDP and around 12 per cent of the employment. This study is an attempt to identify the consumer behaviour toward retailsector in India. The services offered by the retailers and the importance ofrecognition of consumers’ value system and the discount offered by the retailerare also other important factors of the study.